2011
DOI: 10.1371/journal.ppat.1002391
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Shadoo in Prion Infections Traces a Pre-Clinical Event Inversely Related to PrPSc Accumulation

Abstract: During prion infections of the central nervous system (CNS) the cellular prion protein, PrPC, is templated to a conformationally distinct form, PrPSc. Recent studies have demonstrated that the Sprn gene encodes a GPI-linked glycoprotein Shadoo (Sho), which localizes to a similar membrane environment as PrPC and is reduced in the brains of rodents with terminal prion disease. Here, analyses of prion-infected mice revealed that down-regulation of Sho protein was not related to Sprn mRNA abundance at any stage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 69 publications
(121 reference statements)
3
48
0
Order By: Relevance
“…Although Prnp and Sprn may encode proteins with overlapping activities (as discussed below), their activities are not interrelated to the extent that their expression levels are counterbalanced. The concept that lack of PrP C produces an increase in Sho expression has been excluded previously by protein analyses of the CNS in Prnp 0/0 mice (21,22,29), and here we can exclude that an alteration in Sprn gene dosage (and hence Sho protein level) affects CNS levels of PrP C (Fig. 4).…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…Although Prnp and Sprn may encode proteins with overlapping activities (as discussed below), their activities are not interrelated to the extent that their expression levels are counterbalanced. The concept that lack of PrP C produces an increase in Sho expression has been excluded previously by protein analyses of the CNS in Prnp 0/0 mice (21,22,29), and here we can exclude that an alteration in Sprn gene dosage (and hence Sho protein level) affects CNS levels of PrP C (Fig. 4).…”
Section: Resultsmentioning
confidence: 66%
“…Prior studies have shown that overexpression of wild-type mouse Sho does not alter the outcome of infections with mouse-adapted prion isolates (21)(22)(23)29). On the other hand, a SPRN frame-shift mutation-a putative null allele-was identified in two of 107 vCJD patients but not in 861 controls (30), suggesting a role for Sho in disease susceptibility in humans.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations